(untitled) (Homoeopathy for All, 2025)
Acne vulgaris, a chronic inflammatory skin condition, was effectively managed in a 19-year-old male using individualized classical homeopathy. Silicea 200C, selected through totality of symptoms, led to significant improvement within two months—reducing inflammation, preventing new eruptions, and enhancing skin and emotional health—highlighting homeopathy’s constitutional and holistic benefits